The shape of human squalene epoxidase expands the arsenal against cancer - Andrew J. Brown (Nature Portfolio, 2019)
Abstract Squalene epoxidase (also known as squalene monooxygenase, EC 1.14.99.7) is a key rate-limiting enzyme in cholesterol biosynthesis. Anil Padyana and colleagues report the long awaited structure of human squalene epoxidase (SQLE). They solved the crystal structure of the catalytic domain of human SQLE alone and in complex with two similar pharmacological inhibitors and elucidate their mechanism of action. SQLE is the target of fungicides and of increasing interest in human health and disease, particularly as a new anti-cancer target. Indeed, in a companion paper, Christopher Mahoney and colleagues performed an inhibitor screen with cancer cell lines and identified SQLE as an unique vulnerability in a subset of neuroendocrine tumours, where SQLE inhibition caused a toxic accumulation of the substrate squalene. The SQLE structure will facilitate the development of improved inhibitors. Here, we comment on these two studies in the wider context of the field and discuss possible future directions.